Together Here, Now and Forever: Chinese Immigrants' Belonging in Australia, Family, Ethnicity and Memorialisation. (3rd May 2020) - Forbes-Mewett, Helen; Han, Gil-Soo; Yang Wang, Wilfred
ABSTRACT: This paper investigates end-of-life decisions, ethnic influences and memorialisaton of Chinese immigrants in Melbourne, Australia. Drawing on interviews with 41 participants including 25 individuals and 16 community or industry stake holders, we present insights into what this group experiences and how they negotiate end-of-life choices to accommodate their hybrid circumstances as immigrants. We find evidence of merging cultures that suggests a new Chineseness played out in diverse ways. We also found this group of Chinese had acquired a sense of belonging relating to being together with family and friends that they wished to continue beyond their lived experience. Their adopted new home in Australia provided an opportunity to be together now and forever.